Crash Analysis of the Frontal Structure of a Car Using Explicit Dynamics - Saumyaa Sinha, Shankar Tewari, Rohan Dhawan,NarendiranathBabu T , D. Rama Prabha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Crash analysis is the primary test conducted to determine crashworthiness and eliminate safety concerns in a vehicle. The improvements in roadways and implementation of new design technologies in automobiles, has shifted a tremendous focus on vehicle safety in recent years. Deaths due to road accidents over the years have increased, primarily due to the inability of a car to withstand load and impact forces during collision. Multiple tests to assign passenger cars with a Global New Car Assessment Program rating (NCAP) have been conducted and the result is still inconsequential. This study presents a comparative outlook for a more structurally suitable material. Materials were selected based on previous research conducted. Three different velocities of 40 km/hr, 80 km/hr, 120 km/hr were considered and a simulation to calculate Total Deformation, Equivalent Plastic Strain and Equivalent Stress (Von Mises) was carried out using Explicit Dynamics in ANSYS. Values calculated at these velocities are presented in a tabular form and graphs were made. Inference was drawn and a suggestion for a better material is made.